2020
DOI: 10.1016/j.celrep.2019.12.039
|View full text |Cite
|
Sign up to set email alerts
|

p53 Integrates Temporal WDR5 Inputs during Neuroectoderm and Mesoderm Differentiation of Mouse Embryonic Stem Cells

Abstract: Highlights d WDR5-RbBP5 interaction surface controls ESC-toneuroectoderm organoid differentiation d Wdr5 inhibition stabilizes p53 and activates p53 signaling d Transient Wdr5 inhibition stimulates ESC differentiation toward mesoderm fates via p53

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 60 publications
3
18
0
Order By: Relevance
“…We thus conducted RNA-sequencing using 9-day-old EBs, in which WT and KO cells commit to the similar lineage. Global comparisons using principle components analysis (PCA) and hierarchical clustering analysis revealed that EB replicates in the same group had high reproducibility, and that their identity was close to previously reported neuroectoderm organoids 33 than to other developmental derivatives 34,35 ( Supplementary Fig. 4e, f).…”
Section: Fgf8supporting
confidence: 64%
“…We thus conducted RNA-sequencing using 9-day-old EBs, in which WT and KO cells commit to the similar lineage. Global comparisons using principle components analysis (PCA) and hierarchical clustering analysis revealed that EB replicates in the same group had high reproducibility, and that their identity was close to previously reported neuroectoderm organoids 33 than to other developmental derivatives 34,35 ( Supplementary Fig. 4e, f).…”
Section: Fgf8supporting
confidence: 64%
“…At day 4, cells were counted using Trypan Blue dye, centrifuged at 211 xg and washed with Ca ++ and Mg ++ free 1X DPBS (14190144, Gibco™). 2 × 10 6 viable cells per sample per antibody were processed for CUT&RUN experiment as previously described 46 . Briefly, cells were collected and washed by PBS at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Like WDR5, p53 is highly expressed in ESCs and decreases during differentiation (Lin et al, 2005). We found that WDR5 interacts with p53 (Li et al, 2020). We identified a repressor function for WDR5, in which its transient inhibition triggers mESC misspecification toward the mesoderm lineage under conditions that normally induce neuroectoderm fate, through a p53-dependent mechanism (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 83%
“…We found that WDR5 interacts with p53 (Li et al, 2020). We identified a repressor function for WDR5, in which its transient inhibition triggers mESC misspecification toward the mesoderm lineage under conditions that normally induce neuroectoderm fate, through a p53-dependent mechanism (Li et al, 2020). p53 is most recognized as a regulator of DNA damage and aberrant p53 loss-of-function and gain-of-function (GoF) mutations contribute to tumorigenesis (Giaccia and Kastan, 1998;Haupt et al, 1997;Sabapathy et al, 1997).…”
Section: Introductionmentioning
confidence: 99%